Optical Guided-wave Chemical and Biosensors I - Zourob, Mohammed; Lakhtakia, Akhlesh (Springer Series on Chemical Sensors and Biosensors, Methods and Applications ;, 2009)
For the first time, distinguished scientists from key institutions worldwide provide a comprehensive approach to optical sensing techniques employing the phenomenon of guided wave propagation for chemical and biosensors. This includes both state-of the-art fundamentals and innovative applications of these techniques. The authors present a deep analysis of their particular subjects in a way to address the needs of novice researchers such as graduate students and post-doctoral scholars as well as of established researchers seeking new avenues. Researchers and practitioners who need a solid foundation or reference will find this work invaluable. This first of two volumes contains eight chapters covering planar waveguides for sensing, as well as sensing techniques based on plasmonic waveguides.